Cytogenetic studies in pregnant women - Zavala Coca, Carlos (2015)
Introduction: Prenatal diagnosis includes all diagnosis used to detect congenital alterations in the fetus. Amniocentesis and study of chorionic villus sampling are the most common techniques used in prenatal diagnosis in order to detect chromosomal alterations in a fetus at risk because of mother’s age or presence of ultrasound markers. Objectives: To determine frequency of chromosomopathies and culture success in patients attended in a specialized centre. Design: Retrospective study. Setting: Reprogenetics SAC, Lima, Peru. Participants: Pregnant women with age above 35 years or with ultrasound markers of fetal anomalies. Interventions: In 118 patients attended from June 2007 through August 2010 data of frequency of chromosomopathies and culture success were analyzed as well as mean mother age, gestational age and indications of prenatal cytogenetic study. All amniotic fluid samples were obtained by transabdominal puncture with ultrasound guide and asepsis. Chorionic  villus sampling was obtained from miscarriages. Cells from both amniotic liquid and chorionic villus were cultured in AmnioMax medium in wet oven at 37ºC and 5% CO2 atmosphere during 10 to 12 days. Chromosomes were analyzed by G banding techniques and results were delivered within 15 days of sample collection. Main outcome measures: Cultures success and chromosomopathies found. Results: Fetal karyotypes were obtained in 95,8% of cultures and a chromosomal anomaly was found in 52,2%. Mean maternal age for amniotic fluid study was 33,9 years (range: 23 to 43 years) and mean gestational age from date of last menstrual periods was 16,1 weeks (range 13 to 18 weeks). Mean maternal age for chorionic villus sampling was 35,9 years (range: 26 to 44 years) and mean gestational age 11,8 weeks (range 9 to 18 weeks). Conclusions: In half of samples for fetal karyotype a chromosome abnormality was encountered. Even though number of samples analyzed was low data agree with other authors’ reports.